If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -12 = -1(4x + -6) + 3x Reorder the terms: -12 + 5x = -1(4x + -6) + 3x Reorder the terms: -12 + 5x = -1(-6 + 4x) + 3x -12 + 5x = (-6 * -1 + 4x * -1) + 3x -12 + 5x = (6 + -4x) + 3x Combine like terms: -4x + 3x = -1x -12 + 5x = 6 + -1x Solving -12 + 5x = 6 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -12 + 5x + x = 6 + -1x + x Combine like terms: 5x + x = 6x -12 + 6x = 6 + -1x + x Combine like terms: -1x + x = 0 -12 + 6x = 6 + 0 -12 + 6x = 6 Add '12' to each side of the equation. -12 + 12 + 6x = 6 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 6 + 12 6x = 6 + 12 Combine like terms: 6 + 12 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| -4(6y-5)-y=-2(y-2) | | 3p+13=-29 | | 8x-3=2(x+15) | | 1/10(x+3)=1/4(2-x) | | 4m-3+7m=30 | | 2(x-5)+3=11 | | x+0.8=0.4(x+5) | | 10+2x=50 | | (7x+9)=(6+10x) | | 4x+1.3=6x-1.1 | | 2x-72+x-15=11 | | 2a^2-3a+5=0 | | 2x-1080=2x-11 | | 4(x-4)+2x=6(x+5)-46 | | 8(x-3)=4 | | x-9=-3x-9 | | 2x-72+x-15=2x-11 | | -7(x-4)=21 | | x-15=2x-72 | | 10-2x=50 | | x/4+4/5=5/12 | | 7x-3+3x=9 | | 5(x+7)=4(x-6)+x | | 7x-3+9=3x | | 7x-3=3x | | 6(-7)+x=7(x-7)+7 | | 2x+11=19-2x | | 20(x+3)=4(15+5x) | | 2x-5/8+x=2x+5/2+2 | | -3(2m-9)+7(m-4)=12-9 | | x/2-4=2 | | -6x-x=0 |